An investigation into the nature of, and relationships between, educational objectives as stated and those inherent in related examination questions for auditing courses at South African universities - Smith, P M (College of Accounting, 2016)
This study sets out to investigate the relationship between the stated and inherent auditing course objectives of selected South African universities. The need for congruence between the two is assumed. Stated auditing course objectives were established by means of a survey questionnaire to 17 South African universities. A panel of judges was used to perform an inferential analysis of 3 of these universities' related examination papers to determine their inherent course objectives. In addition, auditing practitioners were surveyed to establish what they considered desirable auditing course objectives at South African universities.